Asuhan Keperawatan Pemberian Intervensi Edukasi Pembatasan Cairan pada Ny. D.S dengan Masalah Overload Cairan di Ruangan HD Melati RSUP. Prof. Dr. R. D. Kandow Manado - Hioda, Putri Amelia; Natalia, Adriani; Larira, Dina Mariana (Mapalus Nursing Science Journal, 2025)
Background. A common problem experienced by patients undergoing haemodialysis who do not comply with fluid restrictions is excess fluid volume in the body. One effort to prevent an increase in the population of chronic kidney disease and excess fluid volume is by providing fluid restriction education. Objective. To increase patient knowledge regarding fluid restrictions and be able to balance the intake and output of chronic kidney disease patients undergoing haemodialysis at RSUP. Prof. Dr R.D. Kandow Manado. Method. This case study was carried out using a nursing care approach which includes assessment, nursing diagnosis, intervention, implementation and evaluation. Results. The main nursing problems that emerged were hypervolemia and knowledge deficits. After being given the educational intervention on fluid restriction as well as fluid monitoring for 6 days, complaints of an enlarged stomach decreased, there was an increase in patient knowledge regarding fluid limitation, which improved after being given education using leaflets. Conclusion. providing fluid restriction education to chronic kidney disease patients undergoing hemodialysis can increase patient knowledge and improve the patient's quality of life. Keywords: Fluid restriction education, haemodialysis, chronic kidney disease.